1984
DOI: 10.1111/j.1365-2761.1984.tb00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative kidney disease: first reported outbreak in North America

Abstract: Proliferative kidney disease (PKD) was diagnosed in rainbow trout, Salmo gairdneri Richardson, at the Hagerman, Idaho, State Fish Hatchery. Wild fish from Riley Creek, one of the hatchery water supplies, were infected with PKD organisms. Clinical signs, gross pathology and histopathology of affected fish were typical of those reported for PKD in salmonids from European hatcheries. In addition to lesions normally seen, we observed a severe vasculitis and occlusion of renal and hepatic vessels. Ultrastructure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
1
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 8 publications
2
32
1
1
Order By: Relevance
“…This fusing of membranes was previously noted by Ferguson & Needham (1978). However, exocytosis of the bodies' contents as described by Smith et al (1984) was never observed in this study, suggesting that it is a relatively rare phenomenon. When the bodies fused with the plasmalemma in this study, their electron-dense contents were not ejected extracellularly; rather the bodies appeared to interact with the plasmalemma, adding, exchanging or removing a substance from it.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…This fusing of membranes was previously noted by Ferguson & Needham (1978). However, exocytosis of the bodies' contents as described by Smith et al (1984) was never observed in this study, suggesting that it is a relatively rare phenomenon. When the bodies fused with the plasmalemma in this study, their electron-dense contents were not ejected extracellularly; rather the bodies appeared to interact with the plasmalemma, adding, exchanging or removing a substance from it.…”
Section: Discussioncontrasting
confidence: 38%
“…When the bodies fused with the plasmalemma in this study, their electron-dense contents were not ejected extracellularly; rather the bodies appeared to interact with the plasmalemma, adding, exchanging or removing a substance from it. Due to the density of the plasmalemma in areas where the bodies fuse, it has been suggested that it is the dense substance of the cell membrane that is being transported (Smith et al 1984). The purpose of this material is unclear although it may be involved in evasion of the immune response or in the physical strengthening of the membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence they are exocytosed (Perkins 1968, Smith et al 1984, Azevedo & corral 1985, Scro & Ford 1990, and may cause host cell lysis (Perkins 1979, Scro & Ford 1990. Alternatively, it has also been suggested that they participate in spore wall formation (Newman et al 1976), and Golgi-derived dense bodies in Paramarteilia orchestiae appear to fulfil this function (Ginsburger-Vogel & Desportes 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Structures resembling haplosporosomes are not confined to haplosporidians, but also occur in Pararnyxa paradoxa (Desportes 1981), in the vegetative stages of myxozoans (Smith et al 1984, Kent & Hedrick 1985, Lom et al 1989, and in the primary cells of Marteilia sydneyi and its relatives (Perkins 1976 (Perkins 1969, Desportes & Nashed 1983, Smith et al 1984, Azevedo & Corral 1987, Larsson 1987, Lom et al 1989, from dense or formative inclusions derived from the spherule (Perkins 1975, Marchand & Sprague 1979, Ball 1980, Ormieres 1980, La Haye et al 1984, Hillman et al 1990), or from MVB (Perkins 1968, 1976, Perkins & Wolf 1976, Seagrave et al 1980, Desportes 1981.…”
Section: Discussionmentioning
confidence: 99%